High‐Power Density Piezoelectric Energy Harvesting Using Radially Strained Ultrathin Trigonal Tellurium Nanowire Assembly. (25th April 2013) - Lee, Tae Il; Lee, Sangmin; Lee, Eungkyu; Sohn, Sungwoo; Lee, Yean; Lee, Sujeong; Moon, Geondae; Kim, Dohyang; Kim, Youn Sang; Myoung, Jae Min; Wang, Zhong Lin
<x xml:space="preserve">Abstract</x> A high‐yield solution‐processed ultrathin (<10 nm) trigonal tellurium (t‐Te) nanowire (NW) is introduced as a new class of piezoelectric nanomaterial with a six‐fold higher piezoelectric constant compared to conventional ZnO NWs for a high‐volume power‐density nanogenerator (NG). While determining the energy‐harvesting principle in a NG consisting of t‐Te NW, it is theoretically and experimentally found that t‐Te NW is piezoelectrically activated only by creating strain in its radial direction, along which it has an asymmetric crystal structure. Based upon this mechanism, a NG with a monolayer consisting of well‐aligned t‐Te NWs and a power density of 9 mW/cm3 is fabricated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>